Dynamics of plasma particles interaction with electric field fluctuations - Chirkov, A.Yu.; Khvesyuk, V.I. (Вопросы атомной науки и техники, 2002)
A study is made of the dynamics of particles interacting with electromagnetic field fluctuations in a plasma in the presence of a magnetic field. Possible mechanism of anomalous transport is analyzed. Estimates of the diffusion coefficient are proposed based on the calculations of particle trajectories.